QUALITY OF LIFE AND PSYCHOLOGICAL WELL-BEING AMONG MOTHERS HAVING CHILDREN WITH MULTIPLE DISABILITIES - Waseem Qayoom Kachroo; Irshad Ahmad Reshi; Mohd Iqbal War (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Abstract Background and Purpose: The Psychological well-being is a multi-dimensional concept it includes various ,aspects such as optimism, self-control, happiness, sense of interests, free of failures, anxiety and loneliness have been considered as the special aspects of well-being) (Bordbar, Nikkar, Yazdani, & Alipoor, 2011).Since the purpose of the study was to assess the Quality of Life (QOL)and Psychological Well-Being of mothers having children with multiple disabilities. Disabilities in children cause not only financial burden but also leads to incomplete state of wellbeing in physical health, psychological health and social health of the families. Methodology: The study used a purposive sampling technique and total sample of 70 mothers having children with multiple disabilities were included in the current study.The instruments used for the data collection was WHOQOL- BREF and PWSB -scale the data was analyzed using descriptive statistics such as frequency distribution, percentages, mean and standard deviations using SPSS 21.0. Results: The result illustrated that 10% mothers demonstrated very poor quality of life while 24% showed their life in neither good nor bad. 5% mothers perceived their life is good and 30% mothers had very good quality of life and very few i.e. 5% of mothers having children with multiple disabilities expressed very poor quality of life. Beside this 31% mother’s poor quality of life and psychological wellbeing .The result of the current study also depicts that poor psychological wellbeing and poor quality of life were observed in between physical disability group as compared to normal group mothers. Mothers having children with multiple disabilities displayed significant impairment in their quality of life especially in the area oflfe. Conclusion: The recent study's findings will be beneficial in creating effective interventions and policy decisions to enhance the quality of life for mothers of children with multiple disabilities